Complex bacterial diversity of Guaymas Basin hydrothermal sediments revealed by synthetic long-read sequencing (LoopSeq) - Hinkle, John E.; Chanton, Jeffrey P.; Moynihan, Molly A.; Ruff, S. Emil; Teske, Andreas (Frontiers in Microbiology, 2025)
Hydrothermal sediments host phylogenetically diverse and physiologically complex microbial communities. Previous studies of microbial community structure in hydrothermal sediments have typically used short-read sequencing approaches. To improve on these approaches, we use LoopSeq, a high-throughput synthetic long-read sequencing method that has yielded promising results in analyses of microbial ecosystems, such as the human gut microbiome. In this study, LoopSeq is used to obtain near-full length (approximately 1,400–1,500 nucleotides) bacterial 16S rRNA gene sequences from hydrothermal sediments in Guaymas Basin. Based on these sequences, high-quality alignments and phylogenetic analyses provided new insights into previously unrecognized taxonomic diversity of sulfur-cycling microorganisms and their distribution along a lateral hydrothermal gradient. Detailed phylogenies for free-living and syntrophic sulfur-cycling bacterial lineages identified well-supported monophyletic clusters that have implications for the taxonomic classification of these groups. Particularly, we identify clusters within Candidatus Desulfofervidus that represent unexplored physiological and genomic diversity. In general, LoopSeq-derived 16S rRNA gene sequences aligned consistently with reference sequences in GenBank; however, chimeras were prevalent in sequences as affiliated with the thermophilic Candidatus Desulfofervidus and Thermodesulfobacterium, and in smaller numbers within the sulfur-oxidizing family Beggiatoaceae. Our analysis of sediments along a well-documented thermal and geochemical gradient show how lineages affiliated with different sulfur-cycling taxonomic groups persist throughout surficial hydrothermal sediments in the Guaymas Basin.